Kinesin-12 POK2 polarization is a prerequisite for a fully functional division site and aids cell plate positioning - Pantelis Livanos; Choy Kriechbaum; Sophia Remers; Arvid Herrmann; Sabine Müller (Nature Communications)
Abstract Division plane positioning in plants relies on the remarkably accurate selection of the cortical division zone (CDZ), earmarked by the preprophase band of microtubules. The PHRAGMOPLAST ORIENTING KINESIN 1 and 2 (POK1/2) play pivotal roles in CDZ maintenance in mitosis and guide the approaching phragmoplast during cytokinesis. Our knowledge regarding the mechanism of POK recruitment and subsequent maintenance is hitherto limited. Here, we report that POK2 arrives at the preprophase band utilizing a secondary microtubule-binding site within its carboxy-terminus. Effective tethering to the plasma membrane is achieved through non-specific electrostatic interactions with phospholipids. Reaching the cortex via premitotic cortical microtubules emerges as a prerequisite for POK2 polarization, as the order and the density of prophase microtubules become particularly relevant in the preprophase band-compromised mutant trm678. POK2 binding to cortical microtubules templates its future position at the cortex and appears critical for adequate division site setup and consequently tissue architecture.